Memory consolidation and reconsolidation in an invertebrate model: The role of the GABAergic system - Carbo, Martin (2009)
Consolidation theory assumes that memories are labile during a limited time window after acquisition, but as time passes, memories become stable and resistant to amnesic agents. However, the vision of immutable memories after consolidation has been challenged. Thus, after the presentation of a reminder, the reactivated old memories become labile and again susceptible to amnesic treatments. This process implies a re-stabilization phase, usually referred to as reconsolidation. Gamma-aminobutyric acid (GABA) is the major inhibitory neurotransmitter both in the Central nervous system (CNS) and in the periphery. A considerable amount of evidence has arisen from different studies regarding the role of the GABAA receptor in diverse behavioral paradigms and tasks. Here, we investigate the role of the GABAergic system on both memory consolidation and reconsolidation phases by using the memory paradigm of the crab Chasmagnathus. In order to achieve such a goal, we design pharmacological-behavioral experiments, which include the administration of classic agonist (muscimol) and antagonist (bicuculline) of the mammals GABAA receptors. The current results show that the systemic administration of muscimol impairs the consolidation and reconsolidation processes. In contrast, the administration of bicuculline improves the consolidation and reconsolidation processes. Furthermore, the co-administration of both drugs blocks the agonist amnesic effect on the consolidation phase. The ubiquity of the neurotransmitter and its receptors in the animal taxa allows us to use the classic agonist-andantagonist administration procedure in this invertebrate. Thus, all the results reported in this paper can be judged as a result of the modulation exerted by the functional state of the GABAergic system in the CNS. To conclude, the results obtained in this report with an invertebrate model represent additional evidences supporting the view that some molecular mechanisms subserving different memory phases could be the basic tools employed by phylogenetically disparate animals.